1999
DOI: 10.1177/000348949910800416
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Lateral Pharyngeal Pouch

Abstract: A patient with dysphagia including symptoms of regurgitation of food and worsening pulmonary symptoms was found to have a lateral pharyngeal pouch. The diagnosis was made by barium swallow study and confirmed by endoscopy. The characteristic barium swallow findings include retention of barium in a sac or diverticulum. Endoscopy showed a pouch in the left lateral pharynx, adjacent to the vallecula. Surgical therapy consisting of endoscopic stapling of the mucosal band separating the pouch from the pharynx was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 7 publications
(7 reference statements)
0
31
0
Order By: Relevance
“…There are descriptions of associated complaints with lateral laryngopharyngeal protrusions, classified as diverticula, like dysphagia [1], cervical aching and odynophagia [15], dysphagia and hoarseness [12], dysphagia, suffocation and cervical discomfort [14] and even the possibility of aspiration after swallowing [13,16]. Bagatzounis and Geyer [17] suggested that a lateral pharyngeal protrusion could be the cause of laryngeal superior nerve neuralgia.…”
Section: Introductionmentioning
confidence: 99%
“…There are descriptions of associated complaints with lateral laryngopharyngeal protrusions, classified as diverticula, like dysphagia [1], cervical aching and odynophagia [15], dysphagia and hoarseness [12], dysphagia, suffocation and cervical discomfort [14] and even the possibility of aspiration after swallowing [13,16]. Bagatzounis and Geyer [17] suggested that a lateral pharyngeal protrusion could be the cause of laryngeal superior nerve neuralgia.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these previous observations, no spontaneous complaints were expressed by the 22 subjects all of them wind instrumentalists with large diverticula. Nevertheless, there are descriptions of complaints associated with lateral laryngopharyngeal diverticula, such as dysphagia (10) , cervical aching and odynophagia (15) , dysphagia and hoarseness (11) , dysphagia, suffocation, and cervical discomfort (9) , aspiration after swallowing (16,28) , laryngeal superior nerve neuralgia (3) , cervical mass (24) , halitosis, and the sensation of a foreign body in the throat (18) . For this reason, all these complaints were directly mentioned to each volunteer, and all of them denied any such complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Diverticula are uncommon in the EI, and they generally are of 4 types: lateral pharyngeal or laryngopharyngeal diverticulum, [31][32][33][34] Zenker's diverticulum, 35 diverticulum or pseudodiverticulum, 40 and KillianJamieson diverticulum 41-43 (Video 2, available online at www.giejournal.org). Diverticula in the EI and esophagus are best studied by barium esophagram.…”
Section: Diverticulamentioning
confidence: 99%